Diversity of endophytic fungi associated with branches of Berchemia discolor in the Limpopo Province of South Africa - Coetzee, Martin Petrus Albertus (University of Pretoria, 2022)
Dissertation (MSc (Microbiology))--University of Pretoria, 2022.